Innovative Advancements in Construction: The Sustainable Promise of Aerated Concrete Incorporating Fly Ash and River Sand - Larik, Maroosha; Kumar, Aneel; Ali, Tauha Hussain; Larik, Rimsha (Civil Engineering Journal, 2025)
Aerated Concrete, or lightweight concrete, is primarily used in construction work for non-load-bearing structures and is typically produced with cement as a primary binding material. Cement production accounts for 7 to 8% of the environmental CO2 emissions. Furthermore, the dumping of industrial waste and the consumption of aggregates disrupt the environment and ecosystem. This research aims at developing sustainable AC by partially substituting cement with FA and hill sand with IRS while maintaining the fundamental properties of aerated concrete. The study was conducted to investigate the physical and chemical properties of the materials and the physical and mechanical properties of aerated concrete. Variations of fly ash, i.e., 10%-70%, were incorporated as a CRM to get optimum FA usage in terms of density and compressive strength. Optimum FA was incorporated as CRM and IRS as sand replacement, used in four variations, i.e., 10% - 25%. Specimens were cured using the conventional curing method and autoclaving for NAAC and AAC, considering both manufacturing processes, CO2 emissions and time limitations in respective curing methods. Conventional curing was performed at 7, 14, and 28 days, while autoclaving was performed at various pressures, i.e., 0.5 bar, 1 bar, and 1.5 bar. The optimum compressive strength of AAC and NAAC was achieved when 20% of the IRS and 50% of FA were replaced with hill sand and cement, respectively, for both AAC and NAAC. Additionally, approximately 32% and 39.3% of CO2 emissions were reduced with 50% FA and 20% river sand replacement with cement for AAC and NAAC specimens. Although AAC demonstrated slightly lower water absorption due to densification through autoclaving, NAAC performed satisfactorily in offering a more cost-effective and energy-efficient alternative.